PEMANFAATAN ARANG AKTIF DARI KULIT BUAH BINTARO (Cerbera Manghas) SEBAGAI ADSORBEN ION LOGAM Mn (II) - Margarita Margarita; Saibun Sitorus; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2017)
There has been research on the utilization of activated charcoal carbon as an adsorben of cerbera manghas shell in metal ions Mn. This research was intended to find the effects of pH value, contact period and to determine the maximum adsorptive capacity Mn metal ions by cerbera manghas shell activated carbon. The adsorption process have been variate of pH 2, 3, 4, 5 dan 6; contact time variation 15, 30, 45, 60 and 75 and 90 minutes; concentration variation 20, 40, 60, 80 and 100 mg/L. The analysis of metal ions Mn concentration by cerbera manghas shell activated carbon by using atomic absorption spectrophotometer (AAS). The result of this research shows that cerbera manghas activated carbon could adsorb metal ion Mn. The optimum condition was achieved at the pH 2 with a number of metal ions that adsorbed at 9,689 mg/L, with optimum period of 90 minutes with a number of metal ions that adsorbed at 9.414 mg/L, as for optimum concentration was achieved at the cosentration 100 mg/L with a number of metal ions that adsorbed at 25,932 mg/L. Keywords : cerbera manghas shell, activated carbon, adsorption, metal ions Mn.